Chapter2-Part2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 15

Topic 2: Difference Equations (II)

4. Second order linear difference equations


Consider the following example.
Example 4.1 (A Multiplier–Accelerator Growth Model). Let Yt denote national income,
Ct total consumption, and It total investment in a country at time t. Assume that for
t = 0, 1, . . . ,
(i) Yt = Ct + It (income is divided between consumption and investment)
(ii) Ct+1 = aYt + b (consumption is a linear function of previous income)
(iii) It+1 = c(Ct+1 − Ct ) (investment is proportional to to the change in consumption),
where a, b, c > 0. Find a second order difference equation describing this national economy.

Solution: We eliminate two of the unknown functions as follows. From (i), we get
(iv) Yt+2 = Ct+2 + It+2 . Replacing It+2 from (iii) we get Yt+2 = Ct+2 + c(Ct+2 − Ct+1 ) =
(1 + c)Ct+2 − cCt+1 . Finally, use (ii) to obtain
Yt+2 − a(1 + c)Yt+1 + acYt = b, t = 0, 1, . . .
The form of the solution depends on the coefficients a, b, c.
The second–order linear difference equation is
xt+2 + a1 xt+1 + a0 xt = bt ,
where a0 and a1 are constants and bt is a given function of t. The associated homogeneous
equation is
xt+2 + a1 xt+1 + a0 xt = 0,
and the associated characteristic equation is
r2 + a1 r + a0 = 0.

This quadratic equation has solutions


1 1 1 1
q q
2
r1 = − a1 + a1 − 4a0 , r2 = − a1 − a21 − 4a0 .
2 2 2 2
When the sign of the discriminant, a21 −4a0 , is negative, the solutions are (conjugate) complex
numbers.
√ Recall that a complex number is z = a + ib, where a and b are real numbers and
i = −1 is called the imaginary unit, so that i2 = −1. The real part of z is a, and the
imaginary part of z is b. The conjugate of z = a + ib is z = a − ib. Complex numbers can
be added, z + z 0 = (a + a0 ) + i(b + b0 ), and multiplied,
zz 0 = (a + ib)(a0 + ib0 ) = aa0 + iab0 + ia0 b + i2 bb0 = (aa0 − bb0 ) + i(ab0 + a0 b).
8
9

For the following theorem we need the modulus of z, ρ = |z| = a2 + b2 , and the angle θ ∈
[−π/2, π/2] such that tan θ = b/a. It is useful to recall the following table of trigonometric
values
θ sin θ cos θ tan θ
0 0 1 0
√ √
π 1 3 3
6 2 2 3
√ √
π 2 2
4 2 2
1
π

3 1

3 2 2
3
π
2
1 0 ∞
For the negative values of the argument θ, use the properties of sine and cosine: sin (−θ) =
− sin θ and cos (−θ) = cos θ. √
For example, the modulus and argument
√ of 1 − i is ρ = 2 and√θ = −π/4, respectively,
since tan√θ = −1/1 = −1. For z = − 3 − i3, the module is ρ = 12 and the argument is
tan θ = 3, hence θ = π/3.
Theorem 4.2. The general solution of
(4.1) xt+2 + a1 xt+1 + a0 xt = 0 (a0 6= 0)
is as follows:
(1) If the characteristic equation has two distinct real roots,
xt = Ar1t + Br2t .
(2) If the characteristic equation has one real double root,
xt = (A + Bt)rt .
(3) If the characteristic equation has complex roots r1,2 = a ± ib
xt = ρt (A cos θt + B sin θt),

where ρ = a2 + b2 , tan θ = ab , θ ∈ [−π/2, π/2].
A and B are arbitrary constants.
Remark 4.3. When the characteristic equation has complex roots, the solution of (4.1)
involves oscillations. Note that when ρ < 1, ρt tends to 0 as t → ∞ and the oscillations are
damped. If ρ > 1, the oscillations are explosive, and in the case ρ = 1, we have undamped
oscillations.
Example 4.4. Find the general solutions of
(a) xt+2 − 7xt+1 + 6xt = 0, (b) xt+2 − 6xt+1 + 9xt = 0, (c) xt+2 − 2xt+1 + 4xt = 0.
Solution: (a) The characteristic equation is r2 − 7r + 6 = 0, whose roots are r1 = 6 and
r2 = 1, so the general solution is
xt = A6t + B, A, B ∈ R.
10

(b) The characteristic equation is r2 − 6r + 9 = 0, which has a double root r = 3. The


general solution is
xt = 3t (A + Bt).
1

(c) The characteristic equation is r2 −2r +4 = 0, with complex solutions r 1 = 2 (2+ −12) =
√ √ √
12

(1 + i 3), r2 = (1 − i 3). Here ρ = 2 and tan θ = − −2 = 3. this means that θ = π/3.
The general solution is  π π 
xt = 2t A cos t + B sin t .
3 3
4.1. The nonhomogeneous equation. Now consider the nonhomogeneous equation
(4.2) xt+2 + a1 xt+1 + a0 xt = bt ,
and let x∗t be a particular solution. It turns out that solutions of the equation have an
interesting structure, due to the linearity of the equation.
Theorem 4.5. The general solution of the nonhomogeneous equation (4.2) is the sum of
the general solution of the homogeneous equation (4.1) and a particular solution x∗t of the
nonhomogeneous equation.
Example 4.6. Find the general solution of xt+2 − 4xt = 3.
Solution: Note that x∗t = −1 is a particular solution. To find the general solution of
the homogeneous equation, consider the solutions of the characteristic equation, m2 − 4 = 0,
m1,2 = ±2. Hence, the general solution of the nonhomogeneous equation is
xt = A(−2)t + B2t − 1.
Example 4.7. Find the general solution of xt+2 − 4xt = t.
Solution: Now it is not obvious how to find a particular solution. We can try with the
method of undetermined coefficients and try with some expression of the form x∗t = Ct + D.
Then, we look for constants a, b such that x∗t is a solution. This requires
C(t + 2) + D − 4(Ct + D) = t, ∀t = 0, 1, 2, . . .
One must have C − 4C = 1 and 2C + D − 4D = 0. It follows that C = −1/3 and D = −2/9.
Thus, the general solution is
xt = A(−2)t + B2t − t/3 − 2/9.
Example 4.8. Find the solution of xt+2 − 4xt = t satisfying x0 = 0 and x1 = 1/3.
Solution: Using the general solution found above, we have two equations for the two
unknown parameters A and B:
A + B + 29

=0
.
−2A + 2B − 31 + 29 = 13
The solution is A = −2/9 and B = 0. Thus, the solution of the nonhomogeneous equation
is
2 t 2
xt = − (−2)t − + .
9 2 9
11

Remark 4.9. The method of undetermined coefficients for solving equation (4.2) suppose
that a particular solution has the form of the nonhomogeneous term, bt . The method works
quite well when this term is of the form
bt , tm , cos bt, sin bt
or linear combinations of them. The concrete form of the particular solution depends also
on the roots of the characteristic polynomial. We give the following directions.
(1) If bt = abt , where b is not a root of the characteristic polynomial, then we try x∗t = Cbt .
(2) If bt = abt , where b is a root of the characteristic polynomial of multiplicity p, then
we try with x∗t = Ctp bt .
(3) If bt = bm tm + bm−1 tm−1 + · · · + b0 is a polynomial of degree m, we distinguish two
cases:
(a) If 1 is not a root of the characteristic polynomial, then we try with x∗t = Cm tm +
Cm−1 tm−1 + · · · + C0 .
(b) If 1 is a root of the characteristic polynomial of multiplicity p, then we try with
x∗t = tp (Cm tm + Cm−1 tm−1 + · · · + C0 ).
Finally, substitute x∗t into the equation and determine the coefficients C’s.
Example 4.10. Solve the equation xt+2 − 5xt+1 + 6xt = 4t + t2 + 3.

Solution: The homogeneous equation has characteristic equation r2 − 5r + 6 = 0, with


two different real roots r1,2 = 2, 3. Its general solution is, therefore, A2t + B3t . To find a
particular solution we look for constants C, D, E and F such that a particular solution is
x∗t = C4t + Dt2 + Et + F.
Plugging this into the equation we find
C4t+2 + D(t + 2)2 + E(t + 2) + F − 5(C4t+1 + D(t + 1)2 + E(t + 1) + F )
+ 6(C4t + Dt2 + Et + F ) = 4t + t2 + 3.
Expanding and rearranging yields
2C4t + 2Dt2 + (−6D + 2E)t + (−D − 3E + 2F ) = 4t + t2 + 3.
This must hold for every t = 0, 1, 2, . . . thus,
2C = 1,
2D = 1,
−6D + 2E = 0,
−D − 3E + 2F = 3.
It follows that C = 1/2, D = 1/2, E = 3/2 and F = 4. The general solution is
1 1 3
xt = A2t + B3t + 4t + t2 + t + 4.
2 2 2
12

Example 4.11. Solve xt+2 − 5xt+1 + 4xt = 4t + t2 + 3.

Solution: The homogeneous equation has characteristic equation r2 − 5r + 4 = 0, with


two different real roots, r1,2 = 1, 4. Its general solution is, therefore, A + B4t . To find a
particular solution we look for constants C, D, E y F such that a particular solution is
x∗t = Ct4t + t(Dt2 + Et + F ).
Plugging this into the equation we find
C(t + 2)4t+2 + (t + 2)(D(t + 2)2 + E(t + 2) + F ) − 5C(t + 1)4t+1
− 5(t + 1)(D(t + 1)2 + E(t + 1) + F ) + 4Ct4t + 4t(Dt2 + Et + F ) = 4t + t2 + 3.
Equating coefficients we find
t4t : 16C − 20C + 4C = 0,
1
4t : 32C − 20C = 1 ⇒ C = ,
12
t3 : D − 5D + 4D = 0,
1
t2 : 8D + E − 10D − 5E + 4E = 1 ⇒ D = − ,
2
1
t : 4D + 8D + 4E + F − 10D − 5D − 10E − 5F + 4F = 0 ⇒ E = ,
4
23
t0 : 8D + 4F + 2F − 5D − 5E − 5F = 3 ⇒ F = .
4
5. Linear systems of difference equations
Now we suppose that the dynamic variables are vectors, Xt ∈ Rn . A first order system of
linear difference equations with constant coefficients is given by
x1,t+1 = a11 x1,t + · · · + a1n xn,t + b1,t
..
.
xn,t+1 = an1 x1,t + · · · + ann xn,t + bn,t
An example is
x1,t+1 = 2x1,t − x2,t + 1
x2,t+1 = x1,t + x2,t + e−t .
Most often we will rewrite systems omitting subscripts using different letters for different
variables, as in
xt+1 = 2xt − yt + 1
yt+1 = xt + yt + e−t .
A linear system is equivalent to the matrix equation
Xt+1 = AXt + Bt ,
13

where
x1,t a11 . . . a1n b1,t
     

Xt =  ...  , A =  ... . . . ...  , B =  ... 


xn,t an1 . . . ann bn,t
We will center on the case where the independent term Bt ≡ B is a constant vector.
5.1. Homogeneous systems. Consider the homogeneous system Xt+1 = AXt .
Note that X1 = AX0 , X2 = AX1 = AAX0 = A2 X0 . Thus, given the initial vector X0 , the
solution is
Xt = At X0 , t = 0, 1, . . .
5.2. Non Homogeneous Systems. Consider the non-homogeneous system
(5.1) Xt+1 = AXt + B,
where B is a constant vector. Assume that there is only one equilibrium point, X 0 . This si
true if |A − I| =
6 0, because then
X 0 = (I − A)−1 B.
Let Yt = Xt − X 0 and rewrite the system in terms of Yt
Yt+1 = Xt+1 − X 0 = AXt + B − X 0 = AYt + AX 0 + B − X 0
= AYt + B − (I − A)X 0 = AYt + B − (I − A)(I − A)−1 B
= AYt ,
thus we get an homogeneous system and the solution is thus Yt = At Y0 or
(5.2) Xt = X 0 + At (X0 − X 0 ).
We have proved the following result.
Theorem 5.1. Suppose that |A − In | =
6 0. Then the solution of the non-homogeneous system
is given by (5.2).
A question arises immediately. To what extent is this result useful? All depends on how
difficult is to compute At . When A is diagonalizable, At = P Dt P −1 for some regular matrix
P formed with eigenvectors of A and where D is a diagonal matrix with eigenvalus in its
diagonal, so Dt is easily computed.
Example 5.2. Find the general solution of the system
    
xt+1 4 −1 xt
=
yt+1 2 1 yt

 
4 −1
Solution: The matrix A = has characteristic polynomial pA (λ) = λ2 −5λ+6,
2 1
with roots λ1 = 3 and λ2 = 2. Thus, the matrix is diagonalizable. It is easy to find the
eigenspaces
S(3) =< (1, 1) >, S(2) =< (1, 2) > .
14

Hence, the matrix P is


     
1 1 −1 2 −1 3 0
P = , P = , D=
1 2 −1 1 0 2
and the solution
  t     
1 1 3 0 2 −1 2 3t − 2t −3t + 2t x0
Xt = X0 =
1 2 0 2t −1 1 2 3t − 2t+1 −3t + 2t+1 y0
Supposing that the initial condition is (x0 , y0 ) = (1, 2), the solution is given by
xt = 2 3t − 2t + 2(−3t + 2t ) = 2t ,
yt = 2 3t − 2t+1 + 2(−3t + 2t+1 ) = 2t+1 .

We give now an alternative method to compute the solution, assuming as before that the
matrix A is diagonalizable, with eigenvalues λ1 , . . . , λn (possibly repeated) and eigenvectors
u1 , . . . , un . Let C1 , . . . , Cn be arbitrary constants. Then
Xth = C1 λt1 u1 + · · · + Cn λtn un
is the general solution of the homogeneous system. This is easy to check by the very definition
of eigen- values and vectors
AXth = C1 λt1 Au1 + · · · + Cn λtn Aun = C1 λt+1 t+1 h
1 u1 + · · · + Cn λn un = Xt+1 .

The general solution of the complete system is Xt = Xth + X 0 .


Example 5.3. In the above example we found that A was diagonalizable, etc. The general
solution is thus (X 0 = 0)    
t 1 t 1
Xt = C 1 3 + C2 2 .
1 2
If we want to find the solution satisfying X0 = (1, 2), then e have to determine suitable
constants C1 and C2 satisfying
     
1 1 1
= C1 + C2 .
2 1 2
Hence C1 = 0 y C2 = 1.

Example 5.4. Find the general solution of the system


      
xt+1 4 −1 xt 1
= +
yt+1 2 1 yt −1

Solution: The fixed point X ∗ is given by


 −1       
−1 −3 1 1 1 0 −1 1 1/2
(I3 − A) B = = =
−2 0 −1 2 2 −3 −1 5/2
15

We could also have found the point without calculating the inverse and solving instead the
system
x = 4x − y + 1
y = 2x + y − 1.
By the example above we already know the general solution of the homogeneous system.
The general solution of the nonhomogeneous system is then
      
xt 2 3t − 2t −3t + 2t x0 − 1/2 1/2
= + .
yt 2 3t − 2t+1 − 1 −3t + 2t+1 y0 − 5/2 5/2
5.3. Stability of linear systems. We study here the stability properties of a first order
system Xt+1 = AXt + B where |I − A| = 6 0.
For the √following theorem, recall that for a complex number z = a + bi, the modulus is
|z| = ρ = a2 + b2 .
Theorem 5.5. A necessary and sufficient condition for system Xt+1 = AXt + B to be g.a.s.
is that all roots of the characteristic polynomial pA (λ) (real or complex) have moduli less
than 1. In this case, any trajectory converges to X 0 = (In − A)−1 B as t → ∞.
We can give an idea of the proof of the above theorem in the case where the matrix A is
diagonalizable. As we have shown above, the solution of the nonhomogeneous system in this
case is
Xt = X 0 + P Dt P −1 (X0 − X 0 ),
where  t
λ1 0 . . . 0

 0 λt2 . . . 0 
D=  ... .. . . ..  ,
. . . 
0 0 . . . λtn
and λ1 , . . . , λn are the real roots (possibly repeated) of pA (λ). Since |λj | < 1 for all j, the
diagonal elements of Dt tends to 0 as t goes to ∞, since λtj ≤ |λj |t → 0. Hence
lim Xt = X 0 .
t→∞

Example 5.6. Study the stability of the system


1
xt+1 = xt − yt + 1,
2
yt+1 = xt − 1.
 
1 −1/2
Solution: The matrix of the system is , with characteristic equation λ2 −
1 0
p
λ+1/2
√ = 0. The (complex) roots are λ 1,2 = 1/2±i/2. Both have modulus ρ = 1/4 + 1/4 =
1/ 2 < 1, hence the system is g.a.s. and the limit of any trajectory is the equilibrium point,
 −1    
0 1 − 1 0 − (−1/2) 1 3
X = = .
0−1 1−0 −1 2
16

Example 5.7. Study the stability of the system


xt+1 = xt + 3yt ,
yt+1 = xt /2 + yt /2.


1 3
Solution: The matrix of the system is , with characteristic equation λ2 −
1/2 1/2
(3/2)λ−1 = 0. The roots are λ1 = 2 and λ2 = −1/2. The system is not g.a.s. However, there
are initial conditions X0 such that the trajectory converges to the fixed point X 0 = (0, 0).
This can be seen once we find the solution
Xt = P Dt P −1 X0 .
The eigenspaces are S(2) =< (3, 1) > and S(−1/2) =< (2, −1) >, thus
   
3 2 −1 1/5 2/5
P = , P = .
1 −1 1/5 −3/5
The solution is !
2t 53 (x0 + 2y0 ) + 21−t 15 (x0 − 3y0 )
 
xt+1
= .
yt+1 2t 51 (x0 + 2y0 ) − 2−t 15 (x0 − 3y0 )
If the initial conditions are linked by the relation x0 + 2y0 = 0, then the solution converges
to (0, 0). For this reason, the line x + 2y = 0 is called the stable manifold. Notice that the
stable manifold is in fact the eigenspace associated to the eigenvalue λ2 = −1/2, since
S(−1/2) =< (2, −1) >= {x + 2y = 0}.
For any other initial condition (x0 , y0 ) ∈
/ S(−1/2), the solution does not converge.
Example 5.8 (Dynamic Cournot adjustment). The purpose of this example is to investigate
under what conditions a given adjustment process converges to the Nash equilibrium of the
Cournot game.
Consider a Cournot duopoly in which two firms produce the same product and face con-
stant marginal costs c1 > 0 and c2 > 0. The market price Pt is a function of the total
quantity of output produced Q = q1 + q2 in the following way
P = α − βQ, α > ci , i = 1, 2, β > 0.
In the Cournot duopoly model each firm chooses qi to maximize profits, taking as given the
production level of the other firm, qj . At time t, firm i’s profit is
πi = q i P − ci q i .
As it is well–known, taking ∂π i /∂qi = 0 we obtain the best response of firm i, which depends
on the output of firm j as follows1
br1 = a1 − q2 /2, br2 = a2 − q1 /2,
1Actually, the best response map is bri = max{ai − qj /2, 0}, since negative quantities are not allowed.
17

α − ci
where ai = , i = 1, 2. We suppose that a1 > a2 /2 and that a2 > a1 /2 in order to have

positive quantities in equilibrium, as will be seen below.
The Nash equilibrium of the game, (q1N , q2N ), is a pair of outputs of the firms such that
none firm has incentives to deviate from it unilaterally, that is, it is the best response against
itself. This means that the Nash equilibrium of the static game solves
q1N = br1 (q2N ),
q2N = br2 (q1N ).
In this case
q1N = a1 − q2N /2,
q2N = a2 − q2N /2.
Solving, we have
4 a1 
q1N =a2 − ,
3 2
N 4 a2 
q2 = a1 − ,
3 2
which are both positive by assumption. As a specific example, suppose for a moment that
α−c
the game is symmetric, with c1 = c2 = c. Then, a1 = a2 = and the Nash equilibrium

is the output
α−c
q1N = ,

α−c
q2N = .

Now we turn to the general asymmetric game and introduce a dynamic component in the
game as follows. Suppose that each firm does not choose its Nash output instantaneously, but
they adjust gradually its output qi towards its best response bri at each time t as indicated
below
q1,t+1 = q1,t + d(br1,t − q1,t ) = q1,t + d(a1 − 12 q2,t − q1,t ),
(
(5.3)
q2,t+1 = q1,t + d(br2,t − q2,t ) = q2,t + d(a2 − 12 q1,t − q2,t ),
where d is a positive constant. The objective is to study whether this tattonement process
converges to the Nash equilibrium.
To simplify notation, let us rename x = q1 and y = q2 . Then, rearranging terms in the
system (5.3) above, it can be rewritten as
xt+1 = (1 − d)xt − d2 yt + da1 ,
(

yt+1 = (1 − d)yt − d2 xt + da2 .


18

It is easy to find the equilibrium points by solving the system


x = (1 − d)x − d2 y + da1 ,
(

y = (1 − d)y − d2 x + da2 .
The only solution is precisely the Nash equilibrium,
  
N N 4 a1  4  a2 
(x , y ) = a2 − , a1 − .
3 2 3 2
Under what conditions this progressive adjustment of the produced output does converge to
the Nash equilibrium? According to the theory, it depends on the module of the eigenvalues
being smaller than 1. Let us find the eigenvalues of the system. The matrix of the system is
1 − d − d2
 

− d2 1 − d
The eigenvalues of the matrix are
d 3d
λ1 = 1 − , λ2 = 1 − ,
2 2
which only depend on d. We have
|λ1 | < 1 iff 0 < d < 4,
|λ2 | < 1 iff 0 < d < 4/3,
therefore |λ1 | < 1 and |λ2 | < 1 iff 0 < d < 4/3. Thus, 0 < d < 4/3 is a necessary and
sufficient condition for convergence to the Nash equilibrium of the one shot game from any
initial condition (g.a.s. system).
19

6. The nonlinear first order equation


We investigate here the stability of the solutions of an autonomous first order difference
equation
xt+1 = f (xt ), t = 0, 1, . . . ,
where f : I → I is nonlinear and I is an interval of the real line. Recall that a function f is
said to be of class C 1 in an open interval, if f 0 exists and it is continuous in that interval. For
example, the functions x2 , cos x or ex are C 1 is the whole real line, but |x| is not differentiable
at 0, so is not C 1 in any open interval that contains 0.
Theorem 6.1. Let x0 ∈ I a fixed point of f , and suppose that f is C 1 in an open interval
around x0 , Iδ = (x0 − δ, x0 + δ).
(1) If |f 0 (x0 )| < 1, then x0 is locally asymptotically stable;
(2) If |f 0 (x0 )| > 1, then x0 is unstable.
Remark 6.2. If |f 0 (x)| < 1 for every point x ∈ I, then the fixed point x0 is globally
asymptotically stable.
Example 6.3 (Population growth models). In the Malthus model of population growth it
is postulated that a given population x grows at constant rate r,
xt+1 − xt
= r, or xt+1 = (1 + r)xt .
xt
This is a linear equation and the population grows unboundedly if the per capita growth rate
r is positive2. This is not realistic for large t. When the population is small, there are ample
environmental resources to support a high birth rate, but for later times, as the population
grows, there is a higher death rate as individuals compete for space and food. Thus, the
growth rate should be decreasing as the population increases. The simplest case is to take a
linearly decreasing per capita rate, that is
 xt 
r 1− ,
K
where K is the carrying capacity. This modification is known as the Verhulst’ law. Then
the population evolves as  r 
xt+1 = xt 1 + r − xt ,
K
which is not linear. The function f is quadratic, f (x) = x(1 + r − rx/K). In Fig. 6.3 is
depicted a solution with x0 = 5, r = 0.5 and K = 20.
We observe that the solution converges to 20. In fact, there are two fixed points of
the equation, 0 (extinction of the population) and x0 = K (maximum carrying capacity).
Considering the derivative of f at these two fixed points, we have
r
f 0 (0) = 1 + r − 2 x = 1 + r > 1,
K x=0
r
f 0 (K) = 1 + r − 2 x = 1 − r.
K x=K
2The solution is xt = (1 + r)t x0 , why?
20

Thus, according to Theorem 6.1, 0 is unstable, but K is l.a.e. iff |1 − r| < 1, or 0 < r < 2.
21

6.1. Phase diagrams. The stability of a fixed point of the equation


xt+1 = f (xt ), t = 0, 1, . . . ,
can also be studied by a graphical method based in the phase diagram. This consists in
drawing the graph of the function y = f (x) in the plane xy. Note that a fixed point x0
corresponds to a point (x0 , x0 ) where the graph of y = f (x) intersects the straight line
y = x.
The following figures show possible configurations around a fixed point. The phase di-
agram is at the left (plane xy), and a solution sequence is shown at the right (plane tx).
Notice that we have drawn the solution trajectory as a continuous curve because it facilitates
visualization, but in fact it is a sequence of discrete points. In Fig. 1, f 0 (x0 ) is positive, and
the sequence x0 , x1 , . . . converges monotonically to x0 , whereas in Fig. 2, f 0 (x0 ) is negative
and we observe a cobweb–like behavior, with the sequence x0 , x1 , . . . converging to x0 but
alternating between values above and below the equilibrium. In Fig. 3, the graph of f near
x0 is too steep for convergence. After many iterations in the diagram, we observe an erratic
behavior of the sequence x0 , x1 , . . .. There is no cyclical patterns and two sequences gener-
ated from close initial conditions depart along time at an exponential rate (see Theorem 6.1
above). It is often said that the equation exhibits chaos. Finally, Fig. 4 is the phase diagram
of an equation admitting a cycle of period 3.

Figure 1. x0 stable, f 0 (x0 ) ∈ (0, 1)


22

Figure 2. x0 stable, f 0 (x0 ) ∈ (−1, 0)

Figure 3. x0 unstable, |f 0 (x0 )| > 1

Figure 4. A cycle of period 3

You might also like